Avaliação da ingesta de vitamina K e estabilidade da anticoagulação em pacientes ambulatoriais com fibrilação atrial - Hillesheim, Suélen Feijó (2022)
Introduction: The role of food and nutrition in the management of clotting disorders is poorly understood. Vitamin K seems to be one of the factors that influence the stability of anticoagulation, but there is controversy about the orientation regarding food consumption an d source of vitamin K for patients using vitamin K antagonists (VKA). Objective: To evaluate vitamin k intake on anticoagulation stability in outpatients with atrial fibrillation. Method : coorte study , with data collection between January and December 2021. The sample consisted of patients with atrial fibrillation (AF) followed up at the anticoagulation outpatient clinic of a University Hospital in the South of Brazil. Q A structured questionnaire was used at the beginning of the study to collec sociodemographic data, clinicians, t lifestyle, medication and laboratory tests. The assessment of vitamin K consumption was performed using a 24hour food recall. The prothrombin time (PT) was evaluated and it was corrected for the international standardiza tion ratio (INR). The anticoagulation history and efficacy for each patient was evaluated using the time in the therapeutic range (TFT), using Rosendaal's Linear Interpolation Method. Patients were followed for two months, in a total of 3 visits (baseline, 30 and 60 days). In all consultations, the RA24h and the PT were measured. Results: Thirtyseven patients participated in the study, with a mean age of 69.0±9.9 years. When categorizing the sample by controlling the therapeutic range time, it was found tha t 22 (59.4%) had low TFT (<60%) and 15 (40.5%) had ideal TFT (≥60%). No difference was found in vitamin K consumption between the groups with ideal or low TFT (median 35.9 µg vs. 30.4 µg, p=0.458). Conclusion: followin a sample of adult patients with AF in outpat ient up and on VKA, dietary intake of vitamin K was not associated with stability of anticoagulation.